2022
DOI: 10.30934/kusbed.979574
|View full text |Cite
|
Sign up to set email alerts
|

Gebelikte Şiddet: Türkiye' de Ölçek Geçerlik ve Güvenirlik Çalışması

Abstract: Objective: Women are more vulnerable to violence during pregnancy and the postnatal period and they are more often subject to violence during these periods. The purpose of this study was to adapt the Abuse Assessment Screen (AAS) and the Tool for Intimate Partner Violence Screening (HITS), which are most frequently used in screening for violence in pregnancy, into Turkish and to examine the factor structure. Methods: This methodological and descriptive study included 259 pregnant women in a public hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Overall, regarding the cultural adaptation of the N-AAS, the CVI demonstrated good scores, indicating the experts’ agreement on the relevance, understandability, and sensitivity of the questions. These findings align with similar observations from the validation of the AAS in Turkey [ 15 ], reinforcing the validity and potential broader utility of the N-AAS in cultures other than the US.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, regarding the cultural adaptation of the N-AAS, the CVI demonstrated good scores, indicating the experts’ agreement on the relevance, understandability, and sensitivity of the questions. These findings align with similar observations from the validation of the AAS in Turkey [ 15 ], reinforcing the validity and potential broader utility of the N-AAS in cultures other than the US.…”
Section: Discussionsupporting
confidence: 88%
“…In a validation study of the AAS conducted in Turkey [ 15 ], the reliability coefficient was reported as KR20 = 0.801, whereas the Greek version of the scale yielded a reliability coefficient of 0.80 [ 41 ]. Therefore, the comparability of the N-AAS result with other studies supports it as a robust and consistent tool for measuring DV among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a validation study of the AAS conducted in Turkey [15], the reliability coefficient was reported as KR20=0.801, whereas the Greek version of the scale yielded a reliability coefficient of 0.80 [39]. Therefore, the comparability of the N-AAS result with other studies supports it as a robust and consistent tool for measuring DV among pregnant women.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have introduced tools, instruments, or questionnaires for detecting pregnancy-related DV in Nepal [10, 12, 13]. The Abuse Assessment Screen (AAS), originally developed in the United States [14], has been validated in different countries, including Turkey, Greece, and Spain, demonstrating its effectiveness as a simple tool [15–17]. However, formal validation of the AAS is still lacking in LMICs, including Nepal.…”
Section: Introductionmentioning
confidence: 99%